VAPE MARKETING STRATEGY AT OWL VPORIZER STORE IN BANGKINANG CITY - Febri Fitrayansyah; Zulher Zulher; Henrizal Henrizal (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine what the most efective marketing strategy in vape marketing at the OWL Vaporizer Store in Bangkinang City. The types and sources of data in this study are primary data in the form of data collected directly during the research and secondary data in the form of data collected by tracing documents, files and records that have been published. Data collection techniques using interviews, FGD (Focus Group Discussion) and mapping with strength maps, weaknesses, opportunity and threats to determine the advantages of an effective strategy. The key success factor og marketing vape products at OWL Vaporizer Store in Bangkinang City lies in its strengths, namely sklilled OWL Vaporizer Store in Bangkinang City shop owners, with weaknesses in the form of promotions carried out by business owners at OWL Vaporizer Store in Bangkinang City which are less intensive. Meanwhile, business opportunities are the form of consumer behavior oriented to the vape brands being offered, with threats in the form of an unstable local economy. Based on the research results, it shows that the map of the strength position of the vape product marketing strategy at OWL Vaporizer Store in Bangkinang City is in quadrant I as a market leader, namely a strategy to support aggressive growth.